The Relationship Between Duration Disease and Glucose Blood Related to Subjective Compliance in Diabetes Mellitus - Nur Lailatul Lathifah (Universitas Airlangga, 2017)
Diabetes mellitus is often called the silent killer because it can affect all the organs of the body and cause several kinds of complaints. In 2013, Tambaksari Sub-district, Surabaya city has high DM case and become health problem because it has DM prevalence rate exceeding East Java prevalence 2,1% and bigger than DM prevalence rate in Indonesia that is 1.5%. The purpose of this study was to analyze the duration of disease and blood sugar levels with subjective complaints in patients with type 2 diabetes in Puskesmas Rangkah and Pacarkeling Surabaya. This research uses analytic observational with cross sectional method. The sample in this research that is patient of type 2 DM as much as 50 sample. The sampling technique was done by Simple Random Sampling, the researcher conducted the interview with the help of questionnaire. Data analysis using Chi Square test. Dependent variable in this research is subjective complaint, while the independent variable is disease duration and blood sugar level. Result of research indicate that there is correlation between duration of disease with subjective complaint in patient Type 2 DM (p = 0.049) and blood sugar level with subjective complaint In patients with type 2 diabetes (p = 0.004). Based on the analysis it can be concluded that there is a relationship between the duration of the disease and blood sugar levels with subjective complaints in patients with Type 2 diabetes. To the puskesmas in order to increase knowledge and information to patients with type 2 diabetes mellitus diabetes mellitus in the form of complications and how to handle it. Keywords:type 2 diabetes mellitus, disease duration, glucose blood, subjective complaint